2007
DOI: 10.1021/la701703c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Size Exclusion Chromatography Support by Surface Initiated Aqueous Atom Transfer Radical Polymerization

Abstract: We report the use of aqueous surface-initiated atom transfer radical polymerization (SI-ATRP) to grow polymer brushes from a "gigaporous" polymeric chromatography support for use as a novel size exclusion chromatography medium. Poly(N,N-dimethylacrylamide) (PDMA) was grown from hydrolyzable surface initiators via SI-ATRP catalyzed by 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA)/CuCl. Grafted polymer was characterized semiquantitatively by ATR-FTIR and also cleaved and quantitatively characterized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…The general synthetic steps for the ATRPbased synthesis of EIC stationary phases are adapted from Jayachandran et al (2002) and Coad et al (2006) as follows. The Toyopearl 1 AF-Amino-650M base matrix (supplied as a gift from Tosoh Biosep Inc., Montgomeryville, PA) was prepared for grafting by converting the surface amine groups into hydroxyl groups by reacting with ring-opening d-gluconolactone in anhydrous solvent (Narain and Armes, 2003).…”
Section: Synthesis Of Eic Stationary Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The general synthetic steps for the ATRPbased synthesis of EIC stationary phases are adapted from Jayachandran et al (2002) and Coad et al (2006) as follows. The Toyopearl 1 AF-Amino-650M base matrix (supplied as a gift from Tosoh Biosep Inc., Montgomeryville, PA) was prepared for grafting by converting the surface amine groups into hydroxyl groups by reacting with ring-opening d-gluconolactone in anhydrous solvent (Narain and Armes, 2003).…”
Section: Synthesis Of Eic Stationary Phasementioning
confidence: 99%
“…Reactions for production of end-grafted PDMA layers by surface-initiated ATRP and saponification by sodium hydroxide. Saponification over time periods of several hours was used to vary the graft density at constant molecular weight according to the method described in Coad et al (2006). Exhaustive cleavage of graft polymer for the purpose of characterization was accomplished by hydrolysis over a 3-week period.…”
Section: Eic Column Packingmentioning
confidence: 99%
“…In membrane science, SI-ATRP has been used for the surface modification of filters and membranes composed of polycarbonate [39], nylon [40], porous alumina [41], and fluorinated nanofibres [42] as well as molecular transport through silica-based colloidal films [43]. Finally, in separation science, SI-ATRP has been used as a modifier of chromatographic stationary phases including silica beads [44,45], capillaries [46,47], and beaded polymeric stationary phases [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…4-Vinylbenzyl N,N-diethyldithiocarbamate (VBDC) was synthesized by the reaction of p-chloromethylstyrene (Seimi Chemical Industry, Tokyo) with N,N-diethyldithiocarbame sodium (Tokyo Kasei Organic Chemicals, Tokyo) in acetone. Details concerning the synthesis and purification of VBDC were given elsewhere [22]. 2,2 0 -Azobis (4-methoxy-2,4-dimethylvaleronitrile) (V-70; Wako Pure Chemical Industries, Ltd., Tokyo) and potassium persulfate (KPS; Kanto Chemicals, Tokyo) was purified by crystallization from water.…”
Section: Methodsmentioning
confidence: 99%
“…We found that photo-induced atom transfer radical polymerization (ATRP) of DC groups in the presence of copper(I) bromide (CuBr)/2,2 0 -bipyridine (bpy) proceeded with living radical mechanism [21]. There are recently reports concerning polymer brush synthesis by grafting-from approach using the radical initiators on the surface by means of ATRP [22,23]. Surface properties can be easily modified by varying the composition of the polymer brush, grafting density, and the degree of polymerization.…”
Section: Introductionmentioning
confidence: 99%